The use of speech act during 2024 President Candidates Electoral Debate (LingPoet: Journal of Linguistics and Literary Research, 2024)
This research aims to examine the use of speech acts carried out during the 2024 President Electoral Debate, using Pragmatic and Grounded theory approaches by analyzing phrases that contain all type of speech acts. The study analyses all three presidential candidates in the 2024 President Candidates Debate. Through a systemic analysis, the article sheds light on the linguistic strategies employed by each candidate to convey their messages to the public. The findings contribute to the understanding of the speech act’s importance in communicating one’s message, specifically during the Presidential Candidates Debate